Journal review mentoring as an improvement in postgraduate students' competency in critical journal analysis - Anye Widuri; Nurul Jannah Lailatul Fitria (Jurnal Abmas, 2025)
Students enrolled in higher education institutions are obligated to adhere to the Tri Dharma of Higher Education. Higher Education is a place that produces research and scientific development of the highest potential and excellence. Students are required to possess skills in conducting research, analyzing data, compiling scientific papers, and publishing their findings. In particular, postgraduate students are not only needed to create scientific documents but must also possess the expertise to review journals and books. S2 students who have received knowledge related to the preparation of scientific papers and publications need new knowledge and techniques associated with the scope of scientific articles. One of the things needed is knowledge about journal reviews. The purpose of this study is to enhance graduate students' understanding and expertise in conducting thorough and effective journal reviews. Automatically increase understanding and expertise in writing and publishing scientific journals with a reputable national and international scope. Community service activities, such as assisting with scientific journal reviews, are conducted to enhance the competence of graduate students in critically analyzing scientific journals. The results of questionnaires and interviews showed that partners experienced changes and increased understanding related to journal review. All partners agree to gradual and continuous assistance.   Abstrak Mahasiswa dalam naungan perguruan tinggi wajib dan harus patuh dalam Tri Dharma Perguruan Tinggi. Perguruan Tinggi menjadi wadah yang menghasilkan bentuk penelitian dan pengembangan ilmu pengetahuan yang memiliki potensi dan unggul. Mahasiswa dituntut keterampilan dalam melakukan penelitian, menganalisa, menyusun karya ilmiah, dan mempublikasikan. Khususnya pada mahasiswa pascasarjana tidak hanya dituntut untuk membuat karya ilmiah namun harus memiliki keahlian untuk melakukan review jurnal dan buku. Mahasiswa S2 yang pernah menerima ilmu terkait penyusunan karya ilmiah dan publikasi membutuhkan ilmu dan teknik baru terkait lingkup artikel ilmiah. Salah satu yang dibutuhkan pengetahuan tentang review jurnal. Tujuan penelitian ini untuk meningkatkan pemahaman dan keahlian mahasiswa pascasarjana dalam melakukan review jurnal dengan tepat. Secara otomatis meningkatkan pemahaman dan keahlian dalam menulis dan mempublikasi jurnal ilmiah dilingkup nasional dan internasional bereputasi. Kegiatan pengabdian masyarakat berupa pendampingan review jurnal ilmiah dilaksanakan sebagai upaya peningkatan kompetensi mahasiswa pascasarjana dalam melakukan analisis kritis terhadap jurnal ilmiah. Pada hasil kuesioner dan wawancara menunjukkan mitra mengalami perubahan dan peningkatan pemahaman terkait review jurnal. Seluruh mitra setuju adanya pendampingan yang bertahap dan berkelanjutan. Kata Kunci: analisis kritis; kompetensi; review jurnal